A Muscle Biosignature Differentiating Between Limb-Girdle Muscular Dystrophy and Idiopathic Inflammatory Myopathy on Magnetic Resonance Imaging - Hsu, Wen-Chi; Lin, Yu-Ching; Chuang, Hai-Hua; Yeh, Kun-Yun; Chan, Wing P.; Ro, Long-Sun (Frontiers in Neurology, 2021)
Background: The overlapping clinical presentations of limb-girdle muscular dystrophy (LGMD) and idiopathic inflammatory myopathy (IIM) make clinical diagnosis challenging. This study provides a comprehensive evaluation of the distributions and characteristics of muscle fat substitution and edema and aims to differentiate those two diseases. Methods: This retrospective study reviewed magnetic resonance imaging (MRI) of seventeen patients with pathologically proved diagnosis, comprising 11 with LGMD and 6 with IIM. The fat-only and water-only images from a Dixon sequence were used to evaluate muscle fat substitution and edema, respectively. The degrees of muscle fat substitution and edema were graded and compared using the appropriate statistical methods. Results: In LGMD, more than 50% of patients had high-grade fat substitution in the majority of muscle groups in the thigh and calf. However, less than 50% of IIM patients had high-grade fat substitution in all muscle groups. Moreover, LGMD patients had significantly higher grade fat substitution than IIM patients in all large muscle groups (p < 0.05). However, there was no significant difference in edema in the majority of muscle groups, except the adductor magnus (p = 0.012) and soleus (p = 0.009) with higher grade edema in IIM. Additionally, all the adductor magnus muscles in LGMD (100%) showed high-grade fat substitution, but none of them showed high-grade edema. Conclusions: MRI could be a valuable tool to differentiate LGMD from IIM based on the discrepancy in muscle fat substitution, and the adductor magnus muscle could provide a biosignature to categorizing LGMD.